Surgical alternative to tracheoesophageal prosthesis for voice preservation in selected hypopharyngeal carcinoma - Chaudhary, Neena; Jaitly, Shweta; Verma, Rajeev Kumar; Gupta, Shashank; Chaudhary, Para (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Pearson’s near-total laryngectomy (NTL) is a voice- preserving alternative to total laryngectomy in patients with advanced but localized laryngeal and hypopharyngeal cancers, wherein lung- powered speech is achieved by creation of a dynamic biological trachea-pharyngeal shunt. Report our experience with NTL in a series of 24 patients. Methods: A prospective case series analysis was done at VMMC and Safdarjung Hospital from January 2014- September 2019 after attaining ethical clearance. Twenty-four patients with lateralized, locally advanced hypopharyngeal carcinoma, not involving interarytenoid and post- cricoid areas were included in the study. Patients who had involvement of the post cricoid region, interarytenoid region or involvement of bilateral cricoarytenoid units were excluded from the study. The subjects underwent Pearson’s NTL and were followed- up to examine for disease- control and functional results. Results: 22 patients (91.6%) attained a good quality voice following surgery with 2 patients (8.3%) developing minor aspiration problems. 1 patient (4.16%) developed local recurrence after 5 months. Surgical complications were surgical site infection (20.8%), pharyngocutaneous fistula (16.67%) and shunt stenosis (4.16%). Conclusion: NTL is an oncologically safe alternative to total laryngectomy in selected patients and is capable of achieving excellent functional results with minimal surgical complications and post-operative maintenance.